Polymer modified concrete impact on the durability of infrastructure exposed to chloride environments. (24th January 2022) - Mohammed, Hazha; Giuntini, Francesca; Sadique, Monower; Shaw, Andy; Bras, Ana
Highlights: Limited knowledge on impact of polymer modified concrete on corrosion of RC. Seven types of recyclable thermoplastic polymers where tested. Polymers can stop free chlorides inside concrete. Abstract: A limited number of studies are available on the impact of polymer modified concrete on the corrosion effect of Reinforced Concrete (RC) structures, such as bridges exposed to maritime environments or de-icing salts. The aim of this research was to analyse the influence of polymers on the mechanical and durability properties of concrete. Seven types of recyclable thermoplastic polymers PCL, Polymorph, LDPE/EVA granular, LDPE/EVA powder, GPE, N-228 and TPE were used as fine aggregate replacement (3 and 5%). The impact of the molecular weight and structure, size, shape and surface texture of polymers on the fresh and hardened properties of concrete were evaluated. All concretes were designed for a compressive strength higher than 50 MPa. The results show that polymer modified concrete makes the concrete suitable for conventional reinforced concrete manually compacted and heavily reinforced sections with vibrations. Adding granular and powder form of polymers lead to a 2–15% strength increase. For most of the polymers studied, their effect on preventing water migration via capillarity seems to occurr 2–3 days after exposing concrete to water. The substitution of natural fine aggregates with some polymers lead to a reduction of chloride ion migration into the concrete samples, indicating that some of them stop free chlorides inside concrete. 5% LDPE/EVA leads to the higher restricted movement of free chloride migration as the coefficient decreased by 64% in comparison to plain concrete.